Revisiting Immigration Apparatus’ Code of Ethics By Panca Bhakti Insan Imigrasi Values Internalisation - Sri Kuncoro Bawono; Bobby Briando; Sohirin Sohirin (Yayasan Rumah Peneleh, 2021)
This paper aims to revisit the current Immigration Apparatus’ Code of Ethics that is gradually losing its spirit, namely Panca Bhakti Insan Imigrasi, amidst the modernisation and globalization. This research is a library research where data and information were collected and analysed through literature study. The analyses comprise abstraction of knowledge, idea, and thought which are available in academic literatures. There are five core values which are stated in Panca Bhakti Insan Imigrasi:taqwaor piety, upholding honor, intellect, self-integrity, and innovation. Immigration apparatus needs to revisit those values hierarchically. The taqwavalue is an absolute value that will derive the other four values.